ALPPS versus two-stage hepatectomy for colorectal liver metastases—–a comparative retrospective cohort study - Bednarsch, Jan (World J Surg Oncol, 2020)
ABSTRACT: BACKGROUND: Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) and two stage hepatectomy with inter-stage portal vein embolization (TSH/PVE) are surgical maneuvers applied in patients with advanced malignancies considered unresectable by means of conventional liver surgery. The aim of this report is to compare the oncologic outcome and technical feasibility of ALPPS and TSH/PVE in the scenario of colorectal liver metastases (CRLM). METHODS: All consecutive patients who underwent either ALPPS or TSH/PVE for CRLM between 2011 and 2017 in one hepatobiliary center were analyzed and compared regarding perioperative and long-term oncologic outcome. RESULTS: A cohort of 58 patients who underwent ALPPS (n = 21) or TSH/PVE (n = 37) was analyzed. The median overall survival (OS) was 28 months and 34 months after ALPPS and TSH/PVE (p = 0.963), respectively. The median recurrence-free survival (RFS) was higher following ALPPS with 19 months than following TSH/PVE with 10 months, but marginally failed to achieve statistical significance (p = 0.05). There were no differences in morbidity and mortality after stages 1 and 2. Patients undergoing ALPPS due to insufficient hypertrophy after TSH/PVE (rescue-ALPPS) displayed similar oncologic outcome as patients treated by conventional ALPPS or TSH/PVE (p = 0.971). CONCLUSIONS: ALPPS and TSH/PVE show excellent technical feasibility and comparable long-term oncologic outcome in CRLM. Rescue ALPPS appears to be a viable option for patients displaying insufficient hypertrophy after a TSH/PVE approach.